2013
DOI: 10.1007/s00018-013-1270-z
|View full text |Cite
|
Sign up to set email alerts
|

ING1 and ING2: multifaceted tumor suppressor genes

Abstract: Inhibitor of Growth 1 (ING1) was identified and characterized as a "candidate" tumor suppressor gene in 1996. Subsequently, four more genes, also characterized as "candidate" tumor suppressor genes, were identified by homology search: ING2, ING3, ING4, and ING5. The ING proteins are characterized by a high homology in their C-terminal domain, which contains a Nuclear Localization Sequence and a Plant HomeoDomain (PHD), which has a high affinity to Histone 3 tri-methylated on lysine 4 (H3K4Me3). The ING protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 120 publications
0
67
0
Order By: Relevance
“…ASCL1 (MASH1), a transcription factor with critical roles in neuronal commitment and in fibroblastneuron in vitro transdifferentiation was essential for hESC-derived neural lineage development (18). Enrichment of shRNAs during NPC generation is illustrated by shRNAs silencing ING5, a tumor suppressor protein that inhibits growth of various cell types (19).…”
Section: Resultsmentioning
confidence: 99%
“…ASCL1 (MASH1), a transcription factor with critical roles in neuronal commitment and in fibroblastneuron in vitro transdifferentiation was essential for hESC-derived neural lineage development (18). Enrichment of shRNAs during NPC generation is illustrated by shRNAs silencing ING5, a tumor suppressor protein that inhibits growth of various cell types (19).…”
Section: Resultsmentioning
confidence: 99%
“…We identified several genes encoding proteins known to be involved in cell cycle regulation to be dysregulated. CDKN1A (fold change (fc = −4.94), inhibitor of growth family member 4 and 5 (ING4) (fc = 2.94) and (ING5) (fc = 2.13), tumour protein and TP53 inducible protein 3 (TP53I3) (fc = 2.92), centromere protein O (CENPO) (fc = −2.21) and proteasome activator complex subunit 3 (PSME3) (fc = −2.26)19, 20, 21, 22 were significantly altered in CLL compared to healthy donor samples (Figure 3A and Supporting Information). In addition, genes encoding proteins involved in centrosome assembly and function such as centromere protein T (CENPT) (fc = 2.94) and centromere protein J (CENPJ) (fc = 2.08) were up‐regulated in CLL compared to healthy samples (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study found that inhibitors of growth (ING) 1b may decrease osteoblast marker expression, including Runx2 (Bigot et al, 2015). ING1, a member of the ING family, has been described as a type II tumor suppressor that can regulate cell growth, apoptosis, chromatin remodeling, senescence, cell cycle regulation, and DNA repair (Garkavtsev et al, 1998;Guérillon et al, 2013). The human ING1 gene contains three exons and is located at chromosome 13q33-34 Feng et al, 2002).…”
Section: Introductionmentioning
confidence: 99%